MobMouse application - Muhammad Syahmi, Mohd Khairul Muzammil (2019)
The age of wireless is growing rapidly along with the growing technologies. There are times where we as the users that have faced some unwanted incident that could interrupt us from our work and productivity. For instance, our laptop touchpad where it can become malfunction due to hardware or software issues which forced us to either borrow other people’s laptop or mouse, or bring own backup mouse that increase the number of devices carried, having a wireless mouse with dead battery and to be free from cables. This will affect our time and productivity when working. The idea is to develop a mobile application called MobMouse Application which functions as a touchpad by using smartphone’s screen. The MobMouse Application can work well with the present of a wireless network such as WiFi, a PC to communicate with the smartphone that are connected in the same network, an Android smartphone with Android OS version 4.0 Ice Cream Sandwich and above installed and a dedicated UDP port opened on the PC to allow communication between the PC and the smartphone. The methodology used is Rapid Application Development (RAD) that takes advantages of prototyping and code reuse which reduce the development time of the project. The expected results from the MobMouse Application are noted. Lastly, the reason for developing MobMouse application is to overcome the issue of having a malfunction laptop’s touchpad, to overcome a dead battery wireless mouse, to avoid cable management and to reduce the amount of device carried and to determine whether the MobMouse application aligns with the objectives and requirements, to list down the limitations or constraints discovered during MobMouse application’s development and to suggest any future improvement which can benefit the MobMouse application in future versions.